Metal magnetic powder, composite magnetic body, and electronic component
Patent Information
- Application Number
- JP2023140393
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 金属磁性粉末が、上記の特徴を有することで、ギガヘルツ帯の高周波帯域において、高い透磁率と、高信頼性(周波数による透磁率の変化が小さい)とを両立して得ることができる。
Smart Images

Figure 2025034172000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a metal magnetic powder containing metal nanoparticles mainly composed of Co, a composite magnetic body, and an electronic component. [Background technology]
[0002] In recent years, the operating frequencies of high-frequency circuits included in various communication devices such as mobile phones and wireless LAN devices have reached the gigahertz band (for example, the 3.7 GHz band (3.6 to 4.2 GHz) and the 4.5 GHz band (4.4 to 4.9 GHz)). Examples of electronic components mounted in such high-frequency circuits include inductors, antennas, and filters for suppressing high-frequency noise. For the coils built into such electronic components for high-frequency applications, air-core coils having a non-magnetic core are generally used, but in order to improve the characteristics of electronic components, there is a demand for the development of magnetic materials that can be applied to electronic components for high-frequency applications.
[0003] For example, Patent Document 1 discloses a magnetic material made of metal nanoparticles as a magnetic material for high frequencies. Metal nanoparticles can reduce the number of magnetic domains per unit particle compared to metal magnetic particles on the order of micrometers, and can reduce eddy current loss in the high frequency band. However, even with the magnetic material of Patent Document 1, when the operating frequency exceeds 1 GHz, the magnetic permeability drops drastically (Fig. 2 of Patent Document 1), and magnetic loss increases. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-303298 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure has been made in consideration of the above-mentioned situation, and its purpose is to provide a metal magnetic powder that has high magnetic permeability and small change in magnetic permeability with respect to frequency in the high frequency band of the gigahertz band, and a composite magnetic body and electronic component that contain the metal magnetic powder. [Means for solving the problem]
[0006] In order to achieve the above object, the metal magnetic powder according to the present disclosure is The nanoparticles contain Co as a main component and have an average particle size (D50) of 1 nm or more and 100 nm or less, a Fourier transform image using a lattice image of the nanoparticles has streak-like diffuse scattering, Contains at least one additive element selected from the group consisting of Ru, Ir, Re, Rh, Cr, W, and Mo; The ratio of the total content of the additional elements to the total content of Co and the additional elements is 0.5 wt% or more and 10 wt% or less, The nanoparticles have an average aspect ratio (AR) in a TEM image of 1.4 or more and 3.0 or less.
[0007] When the metal magnetic powder has the above characteristics, it is possible to obtain both high magnetic permeability and high reliability (small change in magnetic permeability due to frequency) in the high frequency band of the gigahertz band.
[0008] The average size of the domains present inside the nanoparticles is d Ave As, The average major axis of the nanoparticles is A50, Preferably, d relative to the average major axis of the nanoparticles Ave The ratio (d Ave / A50) is greater than or equal to 0.006 and less than or equal to 0.5.
[0009] With this configuration, the characteristics of high magnetic permeability and high reliability in the gigahertz band are further improved.
[0010] The above-mentioned metal magnetic powder can be contained in a composite magnetic body. An example of the composite magnetic body is a composite magnetic body containing the above-mentioned metal magnetic powder and, for example, a resin. The above-mentioned metal magnetic powder or composite magnetic body can be suitably contained in electronic components for high frequency applications. Examples of the electronic components include, for example, electronic components such as inductors, antennas, and filters. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing a method for measuring the aspect ratio of a particle. [Diagram 2] FIG. 2 is an example of an X-ray diffraction chart of a metal magnetic powder. [Diagram 3] FIG. 3 is a photograph for explaining a Fourier transform image using a lattice image. [Figure 4A] FIG. 4A is an example of an HRTEM image of a nanoparticle. [Figure 4B] FIG. 4B is an example of a Fourier transform image using a lattice image of a nanoparticle. [Figure 5A] FIG. 5A is an example of an HRTEM image (lattice image) of a nanoparticle. [Figure 5B] FIG. 5B is a diagram for explaining a method for analyzing stacking faults. [Figure 5C] FIG. 5C is a schematic diagram showing an example of a stacking fault. [Figure 6] FIG. 6 is a schematic diagram showing a method for measuring the domain size. [Figure 7] FIG. 7 is a schematic cross-sectional view showing an example of a composite magnetic body containing metal magnetic powder. [Figure 8] FIG. 8 is a schematic cross-sectional view showing an example of an electronic component including the composite magnetic body shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings. The embodiment of the present disclosure described below is an example for explaining the present disclosure. Various components according to the embodiment of the present disclosure, such as numerical values, shapes, materials, manufacturing processes, etc., can be modified or changed within a range that does not cause technical problems. In addition, the shapes, etc. shown in the drawings of the present disclosure do not necessarily match the actual shapes, etc. This is because the shapes, etc. may be modified for explanation purposes.
[0013] (Metal magnetic powder) The metal magnetic powder according to this embodiment has a plurality of nanoparticles 2, for example as shown in Fig. 1, and the average particle size of the nanoparticles 2 (i.e., the average particle size of the metal magnetic powder) is 1 nm or more and 100 nm or less. The average particle size of the nanoparticles 2 may be calculated by measuring the circle equivalent diameter of each nanoparticle 2 using a transmission electron microscope (TEM).
[0014] Specifically, the metal magnetic powder is observed at a magnification of 500,000 times or more by TEM, the area of each nanoparticle 2 included in the observation field is measured by image analysis software, and the circular equivalent diameter of each nanoparticle is calculated from the measurement results. At this time, it is preferable to measure the circular equivalent diameters of at least 500 nanoparticles 2, and a cumulative frequency distribution based on the number is obtained based on the measurement results. Then, the circular equivalent diameter at which the cumulative frequency is 50% in the cumulative frequency distribution is calculated as the average particle size (D50) of the nanoparticles 2.
[0015] The average particle size (D50) of the nanoparticles 2 is 100 nm or less, preferably 70 nm or less, or 50 nm or less, and more preferably 30 nm or less. The lower limit of D50 is not particularly limited, but may be, for example, 1 nm or more, or 10 nm or more. When the average particle size of the nanoparticles 2 is set to a predetermined value or less, the magnetic loss tan δ of the metal magnetic powder tends to become smaller. The surface of the nanoparticles 2 may be coated with a coating such as an oxide film or an insulating film.
[0016] In this embodiment, the nanoparticles 2 are preferably not spherical, and the average aspect ratio (AR) in a TEM image of the nanoparticles 2 is 1.4 or more, preferably 1.5 or more. The average aspect ratio is 3.0 or less, preferably 2.7 or less, and more preferably 2.0 or less. The aspect ratio can be measured, for example, as follows.
[0017] Using a TEM, a two-dimensional image of the nanoparticles 2 for which the major axis length, minor axis length and aspect ratio are to be measured is taken, for example, at a magnification of 100,000 times or more. On the taken two-dimensional image, an ellipse 2a circumscribing the nanoparticles 2 is drawn, and the length of the major axis L1 of the ellipse 2a is taken as the major axis length, and the length of the minor axis L2 is taken as the minor axis length. Then, for example, 100 or more nanoparticles 2 in the cross section of the TEM, the aspect ratios are calculated as L1 / L2, and the average of the aspect ratios is taken as the average aspect ratio AR. Also, for example, 100 or more nanoparticles 2, the length of the major axis L1 is calculated, and the average of the lengths of the major axis L1 is taken as the average major axis A50.
[0018] In this embodiment, by setting the average aspect ratio AR within a predetermined range, it is possible to obtain a metal magnetic powder that has high magnetic permeability in the high frequency band of the gigahertz band and in which the change in magnetic permeability with respect to frequency is small.
[0019] The metal magnetic powder containing a large number of nanoparticles 2 contains cobalt (Co) as a main component. That is, the nanoparticles 2 are metal nanoparticles whose main component is Co. Here, the "main component" refers to an element that occupies 80 wt% or more of the metal magnetic powder. The metal magnetic powder preferably contains 90 wt% or more of Co, and more preferably contains 93 wt% or more of Co.
[0020] Furthermore, the metal magnetic powder may contain an additive element M1 in addition to Co (main component). Examples of the additive element M1 include Fe (iron), Ni (nickel), Mg (magnesium), Cu (copper), Na (sodium), magnesium (Mg), Ca (calcium), and amphoteric metals (four elements: aluminum (Al), zinc (Zn), tin (Sn), and lead (Pb)).
[0021] The content of the additive element M1 in the metal magnetic powder is not particularly limited. For example, when the metal magnetic powder contains one or more selected from Fe, Ni, Mg, and Cu as the additive element M1, the ratio of the total content (wt%) of the additive element M1 to the total content (wt%) of Co and the additive element M1 may be 10 ppm or more and 2000 ppm or less. Also, when the metal magnetic powder contains one or more selected from amphoteric metals as the additive element M1, the ratio of the total content (wt%) of the additive element M1 to the total content (wt%) of Co and the additive element M1 may be 10 ppm or more and 10% or less.
[0022] Moreover, the metal magnetic powder contains an additive element M2 in addition to the main component. The amount of additive element M2 added to the metal magnetic powder is not particularly limited. For example, when the metal magnetic powder contains one or more selected from Ru, Ir, Re, Rh, Cr, W, and Mo as the additive element M2, the ratio of the total content (wt%) of the additive element M2 to the total content (wt%) of Co and the additive element M2 is preferably 0.5wt% or more, more preferably 1wt% or more, or may be 2wt% or more. The upper limit of the ratio of the total content (wt%) of the additive element M2 to the total content (wt%) of Co and the additive element M2 is preferably 10wt% or less, and may be 5wt% or less.
[0023] When the metal magnetic powder contains the above-mentioned additive elements M1 and M2, the additive elements M1 and M2 may be present inside the nanoparticles 2 and / or on the surface of the nanoparticles 2. Alternatively, the additive elements M1 and M2 may be isolated from the nanoparticles 2 and contained in the metal magnetic powder.
[0024] The metal magnetic powder may contain other trace elements such as Cl, Br, I, P, C, Si, N, and O. The total content of other trace elements in the metal magnetic powder is less than 20 wt%, and preferably less than 7 wt%.
[0025] The composition of the metal magnetic powder can be measured by composition analysis using, for example, inductively coupled plasma atomic emission spectrometry (ICP-AES), X-ray diffraction (XRD), X-ray fluorescence analysis (XRF), energy dispersive X-ray analysis (EDS), or wavelength dispersive X-ray analysis (WDS), and is preferably measured by ICP-AES. In composition analysis by ICP-AES, first, a sample containing the metal magnetic powder is collected in a glove box, and the sample is added to an acid solution such as HNO3 (nitric acid) and dissolved by heating. Using this dissolved sample, composition analysis by ICP-AES is performed to quantify Co and the added elements M1 and M2 contained in the sample.
[0026] The main component of the metal magnetic powder may be identified based on X-ray diffraction analysis, etc. For example, the volume fraction of each element contained in the metal magnetic powder may be calculated by X-ray diffraction analysis, etc., and the element with the highest volume fraction may be identified as the main component in the metal magnetic powder.
[0027] The metal magnetic powder of this embodiment contains hcp-Co as a Co crystal phase, and may contain fcc-Co or / and ε-Co in addition to hcp-Co. Here, hcp means a hexagonal close-packed structure, and "hcp-Co" means a Co crystal phase having a hexagonal close-packed structure, not an alloy phase. In addition, fcc-Co means a Co crystal phase having a face-centered cubic structure, and ε-Co means a Co crystal phase having a cubic structure different from hcp and fcc. In chunky Co or micrometer-order Co particles, hcp-Co is likely to be generated, but in the case where Co is a fine particle of 100 nm or less, fcc-Co or / and ε-Co is likely to be generated.
[0028] In the metal magnetic powder, it is preferable that each nanoparticle 2 contains hcp-Co as the main phase. Here, the "main phase of the nanoparticle 2 (i.e., the main phase of the metal magnetic powder)" means the crystal phase with the highest content ratio among hcp-Co, fcc-Co, and ε-Co. For example, the ratio of hcp-Co in the metal magnetic powder is W hcp and the ratio of fcc-Co is W fcc If the ratio of ε-Co is Wε, the ratio of hcp-Co is hcp / (W hcp +W fcc +Wε)" is preferably 50% or more, more preferably 70% or more, and even more preferably 80% or more. When the main phase of the metal magnetic powder is hcp-Co, fcc-Co and ε-Co are not necessarily contained in the metal magnetic powder, but fcc-Co and / or ε-Co may be contained as a subphase of Co.
[0029] When the metal magnetic powder contains fcc-Co or / and ε-Co as a subphase, it is preferable that fcc-Co or / and ε-Co are mixed in nanoparticles 2 having hcp-Co as the main phase. In other words, it is preferable that the metal magnetic powder contains nanoparticles 2 having a Co mixed phase structure (a structure containing a main phase and a subphase within a grain) rather than a mixture of single-phase nanoparticles 2 made of hcp-Co and other single-phase nanoparticles made of fcc-Co or ε-Co. In this case, all nanoparticles 2 may have a mixed phase structure, or nanoparticles 2 of hcp-Co (nanoparticles 2 not containing a Co subphase) and nanoparticles 2 of a mixed phase structure (nanoparticles 2 containing a Co subphase) may be mixed.
[0030] The crystal structure of the metal magnetic powder (i.e., the crystal structure of the nanoparticles 2) can be analyzed by X-ray diffraction (XRD). For example, (d) in FIG. 2 is an example of an X-ray diffraction chart of a metal magnetic powder. (a) to (c) in FIG. 2 are all XRD patterns recorded in literature and databases such as ICDD, where (a) is the XRD pattern of ε-Co, (b) is the XRD pattern of fcc-Co, and (c) is the XRD pattern of hcp-Co.
[0031] After obtaining an X-ray diffraction chart of the metal magnetic powder as shown in FIG. 2(d) by 2θ / θ measurement of XRD, profile fitting (peak separation) of the measured X-ray diffraction chart is performed using analysis software for XRD. Then, the separated diffraction peaks are compared with a database to identify the crystalline phase contained in the metal magnetic powder. In the X-ray diffraction chart shown in FIG. 2(d), diffraction peaks appear at the same positions as the XRD pattern shown in FIG. 2(c), and the diffraction peaks indicated by "▼" in FIG. 2(d) are peaks derived from hcp-Co. When the metal magnetic powder contains fcc-Co and / or ε-Co together with hcp-Co, diffraction peaks appear at the positions shown in FIG. 2(a) and FIG. 2(b).
[0032] The proportion of the Co crystalline phase may be calculated based on the integrated intensity of the diffraction peak. Specifically, the diffraction peaks included in the X-ray diffraction chart are identified by profile fitting, and then the integrated intensity of the identified diffraction peaks is calculated. hcp is the integrated intensity of the diffraction peak due to hcp-Co, and W fcc is the integrated intensity of the diffraction peak derived from fcc-Co, and Wε is the integrated intensity of the diffraction peak derived from ε-Co. hcp / (W hcp +W fcc +Wε) can be calculated.
[0033] The presence or absence of a mixed phase structure within the nanoparticles 2 can be confirmed by analysis using a TEM such as high resolution electron microscopy (HRTEM), electron backscatter diffraction (EBSD), or electron diffraction. For example, when analyzing the crystal structure of each nanoparticle 2 by electron diffraction in a TEM, at least 50 nanoparticles 2 are irradiated with an electron beam, and based on the electron diffraction pattern obtained at that time, it is determined whether each nanoparticle 2 has a single phase structure or a mixed phase structure. In this analysis, it is preferable to select nanoparticles 2 that are isolated within the field of view and irradiate them with the electron beam.
[0034] The hcp-Co of the nanoparticles 2 may contain a small amount of additive elements M1 and M2, impurity elements, etc. in solid solution. However, it is preferable that the degree of deviation of the lattice constant of the hcp-Co is 0.5% or less. The "degree of deviation of the lattice constant" is expressed by (|d STD -d f |) / d STD (%), d STD is the lattice constant of hcp-Co recorded in the database, d f is the lattice constant of hcp-Co calculated by analyzing the X-ray diffraction chart of the metal magnetic powder.
[0035] In the case of the metal magnetic powder, a Fourier transform image (FFT image) using a lattice image of the nanoparticles 2 has streak-like diffuse scattering. The FFT image means an image obtained by Fourier transforming a lattice image of the nanoparticles 2 by HRTEM. The lattice image by HRTEM is an image of the nanoparticles 2 in real space, and the image obtained by Fourier transforming the lattice image is an image corresponding to the nanoparticles 2 in reciprocal space. In other words, in the image of the nanoparticles 2 in the reciprocal space, there are streak-like diffuse scattering due to defects and the like, along with diffraction spots representing a periodic structure due to the crystal structure.
[0036] Here, we will explain the patterns that appear in the FFT image using the lattice image. In the FFT image, patterns such as diffraction spots, isotropic diffuse scattering, and streak-like diffuse scattering appear. For example, FIG. 3(a) is an example of a diffraction spot, and the diffraction spot is a spot-like diffraction pattern caused by the arrangement of reciprocal lattice points. On the other hand, FIG. 3(b) to (e) are examples of streak-like diffuse scattering. As shown in FIG. 3(b) to (e), streak-like diffuse scattering is scattering in which the diffraction spot extends in one direction. Note that isotropic diffuse scattering is scattering in which the diffraction spot spreads in all directions so that the outline of the diffraction spot becomes blurred.
[0037] FIG. 4A is an example of a nanoparticle 2 photographed by HRTEM, and FIG. 4B is an example of an image (FFT image) obtained by Fourier transform of a lattice image inside the particle in the HRTEM image of FIG. 4A.
[0038] In the HRTEM image in Figure 4A, streaky contrast can be seen inside nanoparticle 2. This streaky contrast is due to the arrangement of atoms packed on the lattice plane, and the direction perpendicular to the streaky contrast (indicated by the arrow in Figure 4A) corresponds to the c-axis of the crystal lattice.
[0039] The FFT image of the nanoparticle 2 shown in FIG. 4B is an analysis image when an electron beam is incident in the [2,-1,-1,0] direction, and it can be confirmed that the diffraction spot extends in the C* direction, that is, in a direction perpendicular to (0001) in the FFT image. That is, the FFT image of the nanoparticle 2 shown in FIG. 4B has streak-like diffuse scattering extending in the C* direction. The C* direction indicated by the arrow in FIG. 4B is the direction from the origin to (0002) in the reciprocal lattice space, and corresponds to the c-axis in the real space. The direction of the streak-like diffuse scattering of the nanoparticle 2 is not particularly limited, but is preferably a direction perpendicular to (0001) as shown in FIG. 4B.
[0040] In the analysis of the FFT image, when the HRTEM image is taken, it is preferable to set the acceleration voltage to 200 kV or more, and the observation magnification to 500,000 times or more. The incidence direction of the electron beam is not particularly limited, and the nanoparticles 2 may be observed from any incidence direction as long as streak-like diffuse scattering is confirmed in the C* direction. If the FFT image of the nanoparticles 2 is not clear, it may be expanded by connecting lattice images. In addition to the analysis of the FFT image, the diffraction image of the nanoparticles 2 may be analyzed by using the electron beam diffraction method in combination.
[0041] In the metal magnetic powder of this embodiment, the FFT image of the nanoparticles 2 has streak-like diffuse scattering as shown in Figure 4B, which makes it possible to achieve both high magnetic permeability and low magnetic loss in the high frequency band of 1 GHz or more, and also improves reliability (small change in magnetic permeability with frequency).
[0042] Here, the lattice defects of the crystal structure are known to include point defects, line defects, and plane defects. The streak-like diffuse scattering in the nanoparticles 2 is considered to be caused by stacking faults, which are a type of plane defect. In other words, in the metal magnetic powder of this embodiment, it is preferable that the hcp-Co of the nanoparticles 2 has stacking faults.
[0043] The presence or absence of stacking faults can be confirmed by analyzing a lattice image of nanoparticles 2 taken by HRTEM as shown in FIG. 5A. In the lattice image of FIG. 5A, the regions with darker contrast than the surroundings of the image are nanoparticles 2, and the white dots observed inside the nanoparticles 2 are atoms (Co atoms). In the lattice image of FIG. 5A, atoms are arranged at approximately regular intervals along the X-axis direction, and this atomic arrangement along the X-axis direction is arranged along the Z-axis. In other words, the XY plane on which atoms are arranged at approximately regular intervals corresponds to an atomic plane such as the c-plane in a crystal lattice, and the Z-axis perpendicular to the XY plane corresponds to the c-axis in the crystal lattice.
[0044] A method for identifying stacking faults will be described in detail below. First, when analyzing stacking faults, as shown in Fig. 5A, a straight line SL is drawn so as to be perpendicular to an atomic plane such as a c-plane (i.e., parallel to the c-axis) and pass through the center of an arbitrary atom. It is preferable that this straight line SL pass through approximately the center of the nanoparticle 2.
[0045] Next, the position of the atomic arrangement along the c-axis is identified based on the line SL. The photograph shown in FIG. 5B is an enlarged image of a part of the lattice image shown in FIG. 5A. As shown in FIG. 5B, the atomic position when the center of the atom is located on the line SL is "A". The atomic position when the center of the atom is located on the right side of the line SL is "B", and the atomic position when the center of the atom is located on the left side of the line SL is "C". In addition, since atoms are arranged at approximately constant intervals on the atomic plane on the XY plane, all atoms belonging to the same atomic plane may be considered to be present at the same atomic position. For example, when the position of a certain atom present on the line SL is identified as "A", all atoms belonging to the same column in the X-axis direction as the identified atom may be considered to be present at the "A" position.
[0046] In FIG. 5B, it can be seen that the atomic positions are arranged in the order of "ABABCBCBCABABAB" from above to below the line SL. In this way, by identifying the positions of the atoms adjacent to the line SL based on the line SL, the arrangement order of the atomic planes in the c-axis direction can be confirmed. Since Co in the nanoparticle 2 has an hcp structure, a repeating pattern of two types of atomic positions appears in the c-axis direction in the nanoparticle 2. In this embodiment, the repeating pattern of two types of atomic positions is referred to as an "arrangement period". For example, if the atomic planes are arranged in the order of "ABABABAB" along the c-axis, "AB" can be recognized as the unit period.
[0047] A stacking fault is a location where the order of atomic planes is disturbed. A "location where the order of arrangement is disturbed" refers to a location where an atomic plane appears at a position different from the arrangement period, and a location where the arrangement period has changed. For example, in the lattice image of Figure 5B, the arrangement period of the atomic plane indicated by CP1 has switched from "AB" to "CB," and the arrangement period of the atomic plane indicated by CP2 has switched from "CB" to "AB." In other words, the locations indicated by CP1 and CP2 are stacking faults.
[0048] The stacking fault pattern is not limited to the state shown in the lattice image of FIG. 5B, and may be, for example, stacking fault patterns as shown in (a) to (l) of FIG. 5C. The arrow shown at the top of FIG. 5C indicates the c-axis direction, and (a) to (l) indicate the arrangement order of atomic planes in the c-axis direction. In the arrangement orders of (a), (b), (e), (f), (i), and (l) in FIG. 5C, atomic planes appear at positions different from the arrangement period at the underlined locations, and the underlined locations are stacking faults. In addition, in the arrangement orders of (c), (d), (g), (h), (j), and (k) in FIG. 5C, the arrangement period changes at the underlined locations, and the underlined locations are stacking faults.
[0049] The interior of the nanoparticle 2 preferably has two or more domains separated by stacking faults as described above. FIG. 6 is a schematic diagram for explaining the domains and domain sizes inside the nanoparticle 2. In FIG. 6, the atomic planes where atoms are arranged at the "A" positions are shown by solid lines, the atomic planes where atoms are arranged at the "B" positions are shown by dashed lines, and the atomic planes where atoms are arranged at the "C" positions are shown by dashed lines. In FIG. 6, an "AB" arrangement period appears along the c-axis direction, and a part of the atomic planes at the "A" positions is replaced by the atomic planes at the "C" positions. That is, in FIG. 6, three stacking faults exist, and the interior of the nanoparticle 2 is divided into four domains DO1 to DO4 by the three stacking faults.
[0050] The size of each domain contained in the nanoparticle 2 is represented by the maximum length (nm) of the domain in the c-axis direction. Specifically, for the domains located on the outermost side in the c-axis direction (e.g., domains DO1 and DO4 in FIG. 6), the maximum distance from the outer edge of the nanoparticle 2 in the c-axis direction to the stacking fault (e.g., ds1 and ds4 in FIG. 6) is taken as the domain size. Also, for the domains located between two adjacent stacking faults in the c-axis direction (e.g., domains DO2 and DO3 in FIG. 6), the distance between the stacking faults in the c-axis direction (e.g., ds2 and ds3 in FIG. 6) is taken as the domain size.
[0051] The average size of the domains present inside the nanoparticle 2 is d Ave Then, d for the average major axis A50 of nanoparticle 2 Ave The ratio (d Ave / A50) is preferably 0.006 or more and 0.5 or less, more preferably 0.1 or more and 0.5 or less, and even more preferably 0.25 or more and 0.5 or less. Ave By setting / A50 in the above range, it is possible to further improve the magnetic permeability in the high frequency band of 1 GHz or more, and also to further improve the reliability (the change in magnetic permeability due to frequency is small).
[0052] In addition, d AveWhen calculating d, it is preferable to analyze at least 10 arbitrary nanoparticles 2 in which streaky diffuse scattering is confirmed. For example, Ave can be calculated by the following procedure. The size of the domain contained in each nanoparticle 2 in which streak-like diffuse scattering was confirmed is measured, and the average size ds0 of each nanoparticle 2 is calculated (for example, in FIG. 6, ds0=(ds1+ds2+ds3+ds4) / 4). Then, ds0 of each nanoparticle 2 is summed up, and the sum of ds0 is divided by the number of nanoparticles 2 analyzed to obtain d Ave It is sufficient to calculate d Ave In calculating the above, when capturing a lattice image of each nanoparticle, it is preferable to set the acceleration voltage to 200 kV or more and the observation magnification to 500,000 times or more, similarly to the case of acquiring an FFT image.
[0053] (Composite magnetic material 10) Next, the composite magnetic body 10 containing the above-mentioned metal magnetic powder will be described with reference to FIG.
[0054] The composite magnetic body 10 contains the metal magnetic powder having the above-mentioned characteristics and the resin 6, and the nanoparticles 2 constituting the metal magnetic powder are dispersed in the resin 6. In other words, the resin 6 is interposed between the nanoparticles 2, and insulates adjacent particles. The resin 6 may be any resin material having insulating properties, and the material is not particularly limited. For example, the resin 6 may be a thermosetting resin such as an epoxy resin, a phenolic resin, or a silicone resin, or a thermoplastic resin such as an acrylic resin, a polyethylene, a polypropylene, or a polystyrene resin, and is preferably a thermosetting resin.
[0055] The area ratio of the metal magnetic powder in the cross section of the composite magnetic body 10 is preferably 5% to 60%, more preferably 5% to 40%, and even more preferably 10% to 40%.
[0056] The area ratio of the metal magnetic powder in the cross section of the composite magnetic body 10 can be calculated by observing the cross section of the composite magnetic body 10 using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and analyzing the cross section image using image analysis software. Specifically, the cross section image of the composite magnetic body 10 is binarized based on the contrast to distinguish the metal magnetic powder from other parts, and the area ratio of the metal magnetic powder to the entire image (i.e., the area of the observed field of view) can be calculated. The area ratio calculated by the above method can be regarded as the volume ratio (vol%) of the metal magnetic powder contained in the composite magnetic body 10. The volume ratio (vol%) of the metal magnetic powder means the filling rate of the nanoparticles 2 in the composite magnetic body 10.
[0057] When analyzing the nanoparticles 2 contained in the composite magnetic body 10, a thin sample is taken from the cross section of the composite magnetic body 10 using a focused ion beam (FIB), and the thin sample is observed with an HRTEM to obtain a lattice image and an FFT image of the nanoparticles 2. hcp / (W hcp +W fcc +Wε The crystal structure of the metal magnetic powder such as the above may be calculated by performing 2θ / θ measurement by XRD using the composite magnetic body 10 as a measurement sample and analyzing the X-ray diffraction chart of the composite magnetic body 10. The average particle size (D50) of the metal magnetic powder may be calculated by measuring the area of the nanoparticles 2 in the cross section of the composite magnetic body 10. The composition of the metal magnetic powder contained in the composite magnetic body 10 (the composition of the nanoparticles 2) can be analyzed using ICP-AES, XRD, EDS, WDS, etc.
[0058] When the metal magnetic powder contains the additive elements M1 and M2, in the composite magnetic body 10, the additive elements M1 and M2 may be present inside the nanoparticles 2 and / or on the surface of the nanoparticles 2. Alternatively, the additive elements M1 and M2 may be isolated from the nanoparticles 2 and dispersed in the resin 6.
[0059] The composite magnetic body 10 may contain ceramic particles, glass particles, metal particles other than the nanoparticles 2, etc. The shape and dimensions of the composite magnetic body 10 are not particularly limited and may be appropriately determined depending on the application.
[0060] An example of a method for producing the metal magnetic powder and the composite magnetic body 10 will now be described.
[0061] (Metal Magnetic Powder Manufacturing Method) First, nanoparticles 2 are synthesized by thermally decomposing a cobalt complex, which is the precursor of nanoparticles 2. The precursors are octacarbonyldicobalt (Co2(CO)8), Co4(CO) 12 Alternatively, chlorotris(triphenylphosphine)cobalt (CoCl(Ph3P)3), CoBr(Ph3P)3, CoI(Ph3P)3, CoCl(Me3P)3, CoBr(Me3P)3, CoI(Me3P)3, etc. can be used, and it is preferable to use CoCl(Ph3P)3. In addition, when adding an additive element M1 or M2 to the metal magnetic powder, an additive containing the additive element M1 or M2 is prepared, and the additive and precursor are weighed to obtain a desired composition. As the additive, for example, a chloride, a boron hydride compound, or a carbonyl compound containing the additive element M1 or M2 can be used. The content of the additive element M1 or M2 can be controlled by the compounding ratio of the additive.
[0062] Next, the above-mentioned raw materials (precursor, or precursor and additive) and a solvent are put into a reaction vessel such as a separable flask. As the solvent, toluene, ethanol, 1-octadecyl alcohol, oleyl alcohol, anisole, tetrahydrofuran, diphenyl ether, oleylamine, dimethylbenzylamine, tri-n-octylamine, etc. can be used, and oleyl alcohol is preferably used. In addition, a surfactant such as caproic acid, enanthic acid, caprylic acid, lauric acid, tridecyl acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, nonadecylic acid, arachidic acid, henicosylic acid, behenic acid, tricosylic acid, lignoceric acid, melissic acid, oleic acid, nervonic acid, hexylamine, octylamine, octadecylamine, oleylamine, sodium bis-2-ethylhexyl sulfosuccinate, and a silane coupling agent may be added to the reaction solution containing the precursor. An inert gas such as Ar gas or N2 gas is introduced into the reaction vessel to create an inert atmosphere inside the vessel.
[0063] Next, while stirring the reaction liquid with a mechanical stirrer, the reaction liquid is heated by PID control using a temperature controller and a mantle heater until it reaches a predetermined temperature. The heating rate at this time is preferably set to 0.1°C / min to 20°C / min, and the ultimate temperature (retention temperature) is preferably set in the range of 100°C to 350°C. After the reaction liquid reaches the predetermined retention temperature, the reaction liquid is stirred while maintaining the temperature of the reaction liquid for a predetermined time, and the precursor is thermally decomposed. The temperature retention time at this time is preferably set to 0 minutes to 300 minutes.
[0064] The particle size of the nanoparticles 2 depends on the holding temperature and the temperature holding time. For example, the higher the holding temperature is set within the above range, the larger the D50 (A50 is also the same / the same below) of the nanoparticles 2 tends to be. Similarly, the longer the temperature holding time is set within the above range, the larger the D50 of the nanoparticles 2 tends to be. In addition, the d Ave / A50 tends to decrease as the heating rate increases. Also, the average aspect ratio AR of the nanoparticles 2 tends to decrease as the stirring speed increases.
[0065] After a predetermined time has elapsed, the reaction solution is cooled to 30° C., and the generated nanoparticles 2 are washed and collected. Note that a temperature holding time of 0 minutes means that after the reaction solution reaches a predetermined temperature, the reaction solution is cooled without holding the temperature.
[0066] When cleaning the nanoparticles 2, a cleaning solvent in which unreacted raw materials and intermediate products are soluble is used. Specifically, for example, organic solvents such as acetone, dichlorobenzene, or ethanol can be used as the cleaning solvent. In order to suppress oxidation of the nanoparticles 2, it is preferable to subject the cleaning solvent to a degassing treatment. Alternatively, it is preferable to use an organic solvent of ultra-dehydrated grade in which the water content is suppressed to 10 ppm or less as the cleaning solvent. The nanoparticles 2 after cleaning may be collected by sedimentation by centrifugation, or may be collected by using the magnetic force of a magnet.
[0067] For example, when the nanoparticles 2 are washed and collected by centrifugation, the rotation speed is preferably set to 5000 rpm to 20000 rpm, and the processing time per cycle is preferably set to 1 minute to 30 minutes. After centrifugation under these conditions, the supernatant is removed to remove unreacted raw materials and intermediate products. This centrifugation process is preferably repeated, for example, 2 to 5 times.
[0068] The above steps yield a metal magnetic powder. In the above steps, a series of steps from weighing the raw materials to washing and collecting the nanoparticles 2 are carried out in an inert gas atmosphere such as an Ar atmosphere.
[0069] The method for synthesizing the nanoparticles 2 is not limited to the thermal decomposition method of the cobalt complex (precursor) described above. For example, the nanoparticles 2 may be synthesized by reducing the precursor by a polyol method or the like. In this case, the precursor of the nanoparticles 2 may be, in addition to the cobalt complex described above, cobalt acetate (Co(CH3COO)2), cobalt chloride (CoCl2), cobalt chloride hexahydrate (CoCl26H2O), cobalt laurate (CoCH2(CH 11 COO) may also be used.
[0070] (Method of manufacturing the composite magnetic body 10) Next, an example of a method for manufacturing the composite magnetic body 10 will be described.
[0071] The composite magnetic body 10 can be manufactured by mixing the metal magnetic powder, the resin 6, and a solvent, and carrying out a predetermined dispersion process. As the dispersion process, it is preferable to adopt ultrasonic dispersion process or media dispersion process using a bead mill or the like.
[0072] The conditions for the dispersion treatment are not particularly limited, and various conditions may be set so that the nanoparticles 2 are uniformly dispersed in the resin 6. For example, the time for the ultrasonic dispersion treatment may be set in the range of 5 minutes to 30 minutes. In addition, as the solvent to be added during the dispersion treatment, for example, an organic solvent such as acetone, dichlorobenzene, or ethanol may be used, and it is preferable to use a degassed organic solvent or an organic solvent of ultra-dehydrated grade.
[0073] As the media used in the media dispersion process, various ceramic beads can be used, and among the ceramic beads, it is preferable to use zirconia beads, which have a large specific gravity. The filling rate (volume ratio) of the metal magnetic powder in the composite magnetic body 10 can be controlled based on the compounding ratio of the metal magnetic powder and the resin 6.
[0074] The slurry obtained by the above dispersion process is dried in an Ar atmosphere to volatilize the solvent and obtain a dried body. The dried body is then crushed using a mortar or a dry crusher to obtain granules containing the metal magnetic powder and the resin 6. The granules are then filled into a mold and pressurized to obtain the composite magnetic body 10. When a thermosetting resin is used as the resin 6, it is preferable to perform a curing process after pressure molding.
[0075] The series of steps for obtaining the composite magnetic body 10 are also carried out in an inert atmosphere such as an Ar atmosphere, similar to the production of the metal magnetic powder. The method for producing the composite magnetic body 10 is not limited to the above-mentioned pressure molding method. For example, the slurry obtained by the dispersion process may be applied onto a PET film and dried to obtain a sheet-like composite magnetic body 10.
[0076] (Summary of the embodiment) The metal magnetic powder of this embodiment is composed of a collection of nanoparticles 2 that contain Co (preferably hcp-Co) as a main component and have an average particle size (D50) of 1 nm to 100 nm. An FFT image (Fourier transform image) of the nanoparticles 2 has streak-like diffuse scattering. The nanoparticles 2 also contain at least one additive element selected from the group of Ru, Ir, Re, Rh, Cr, W, and Mo, and the ratio of the total content of the additive element to the total content of Co and the additive element is 0.5 wt% or more and 10 wt% or less, and the average aspect ratio (AR) of the nanoparticles 2 is 1.4 or more and 3.0 or less.
[0077] Because the metal magnetic powder has the above characteristics, it is possible to achieve both high magnetic permeability and high reliability (small change in magnetic permeability due to frequency / reduced frequency dependency of magnetic permeability) not only in the megahertz band but also in the high frequency band region of 1 GHz or more. The reason why high magnetic permeability and high reliability can be achieved at the same time is not necessarily clear, but the following points are thought to be related.
[0078] That is, by including nanoparticles containing Co (preferably hcp-Co) as the main component, the metal magnetic powder has a high ferromagnetic resonance frequency, and the particle size of the nanoparticles is in the range of 1 to 100 nm, so that the eddy current loss can be reduced. In addition, the Co nanoparticles 2 have streak-like diffuse scattering due to stacking faults, so that the anisotropic magnetic field is slightly weakened, and the frequency dependency of the magnetic permeability can be reduced while improving the magnetic permeability.
[0079] It is also believed that the inclusion of at least one additive element selected from the group consisting of Ru, Ir, Re, Rh, Cr, W, and Mo may expand the lattice, reduce the magnetic anisotropy, and improve the magnetic permeability. In addition, the average aspect ratio (AR) in the TEM image of the nanoparticles is 1.4 to 3.0, which is believed to further increase the ferromagnetic resonance frequency and contribute to reducing the frequency dependence of the magnetic permeability in the high frequency band.
[0080] Ru, Ir, Re, and Rh are thought to be difficult to dissolve in cobalt and may act as nuclei for epitaxial growth. Cr, W, and Mo are thought to be easy to dissolve in cobalt and may stabilize the hcp structure of cobalt.
[0081] The inside of each nanoparticle 2 is preferably divided into two or more domains by stacking faults. In this case, the average size of the domains present inside the nanoparticle 2 is d Ave As the average long diameter A50 of nanoparticle 2, d Ave The ratio (d Ave / A50) is preferably 0.006 or more and 0.5 or less, more preferably 0.006 or more and 0.1 or less from the viewpoint of increasing the magnetic permeability, and even more preferably 0.1 or more and 0.5 or less from the viewpoint of suppressing the rate of change in magnetic permeability. When the metal magnetic powder satisfies the above range, it is possible to further improve the compatibility between high magnetic permeability and high reliability.
[0082] Both the metal magnetic powder and the composite magnetic body 10 can be applied to various electronic components such as inductors, transformers, choke coils, filters, and antennas, and are particularly suitable for use in electronic components for high-frequency circuits with operating frequencies of 1 GHz or higher (more preferably 1 GHz to 10 GHz).
[0083] An example of an electronic component containing the metal magnetic powder (or composite magnetic body 10) is an inductor 100 as shown in FIG. 8. The inductor 100 has an element body made of the composite magnetic body 10 of this embodiment, and a coil section 50 is embedded inside the element body. A pair of external electrodes 60, 80 are formed on end faces of the element body, and each of the external electrodes 60, 80 is electrically connected to the lead-out sections 50a, 50b of the coil section 50, respectively. Since electronic components such as the inductor 100 contain the metal magnetic powder (composite magnetic body 10) of this embodiment, they have excellent high-frequency characteristics.
[0084] Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments, and various modifications can be made without departing from the gist of the present disclosure.
[0085] For example, in addition to the above-mentioned manufacturing method of the metal magnetic powder, as a method for introducing stacking faults, the nanoparticles 2 may be collected and then subjected to post-treatment using a ball mill or the like. In the post-treatment carried out after the synthesis of the nanoparticles 2, a ball mill is not used to pulverize and refine the nanoparticles 2, but rather to introduce stacking faults inside the nanoparticles 2. In other words, the post-treatment using the ball mill is carried out under gentle conditions such that the nanoparticles 2 are not pulverized.
[0086] Specifically, the post-treatment using a ball mill is performed in a wet manner. That is, the collected nanoparticles 2 are added to a solvent, and the resulting dispersion is put into a rotating container together with the media. The solvent used in this case can be an organic solvent such as hexane, n-octane, and toluene, and it is preferable to use hexane. In addition, it is preferable to use beads having a lower density than Co as the media. As beads having a lower density than Co, for example, glass beads, alumina (Al2O3) beads, zirconia (ZrO2) beads, zircon (ZrO2-SiO2) beads, or stainless steel beads may be used, and it is preferable to use zirconia beads. Furthermore, it is preferable that the average diameter of the media used is 0.05 mm or more and 0.50 mm or less.
[0087] In the post-treatment using a ball mill, the rotation speed of the container is preferably set to 50 rpm or more and 1000 rpm or less, and the treatment time is preferably set to 1 minute or more and 120 minutes or less, more preferably set to 1 minute or more and 20 minutes or less, and even more preferably set to 1 minute or more and 5 minutes or less. EXAMPLES
[0088] The present disclosure will be described in more detail below based on specific examples, although the present invention is not limited to the following examples.
[0089] (Experiment 1) Sample 1 to Sample 5 First, the precursor CoCl(Ph3P)3, oleyl alcohol (solvent), and oleic acid (surfactant) or oleylamine (surfactant) were weighed and placed in a separable flask. The reaction solution was then heated and stirred (stirring speed 1000 rpm) under an Ar atmosphere to thermally decompose the precursor in the reaction solution.
[0090] Specifically, the reaction liquid in the separable flask was heated to 266°C using a mantle heater and a temperature controller while being stirred by a mechanical stirrer. At this time, the temperature rise rate was controlled to 1°C / min. After the temperature of the reaction liquid reached a predetermined temperature, the temperature of the reaction liquid was maintained for 0 to 600 minutes so as to obtain the desired D50, and the thermal decomposition reaction was promoted.
[0091] After cooling the reaction solution to 30°C, ethanol was added to the reaction solution to precipitate the generated nanoparticles. Then, the rotation speed was set to 20,000 rpm, and centrifugation was performed for 10 minutes, and the supernatant was removed to remove undecomposed raw materials and by-products. This centrifugation process was repeated three times to collect the nanoparticles. The collected nanoparticles were recovered to obtain the metal magnetic powders of Samples 1 to 5.
[0092] The entire process from weighing the raw materials to collecting the nanoparticles was carried out under an Ar atmosphere. The D50 of the nanoparticles was controlled by controlling the temperature retention time. In other words, it was confirmed that the longer the temperature retention time, the larger the D50.
[0093] Samples 6 to 10 Metal magnetic powders were obtained in the same manner as Samples 1 to 5, except that the stirring speed during nanoparticle synthesis was adjusted to 500 rpm in order to vary the average aspect ratio AR of the nanoparticles.
[0094] Samples 11 to 15, Sample 21, Sample 22 Metal magnetic powders were obtained in the same manner as Samples 6 to 10, except that the holding time and heating rate were changed so that the nanoparticles would have the desired D50 and streak-like diffuse scattering.
[0095] Samples 16 to 20, 23, and 24 Metal magnetic powders were obtained in the same manner as samples 11 to 15, sample 21, and sample 22, except that RuCl3, the raw material for the additive element, was added so that the ratio of the total content of the additive element to the total content of Co and the additive element was the value shown in Tables 1 and 2.
[0096] Each sample in Experiment 1 was evaluated as follows.
[0097] Measurement of D50, average major axis A50, and average aspect ratio AR of nanoparticles The nanoparticles produced from each sample were observed at a magnification of 500,000 times using a TEM (JEM-2100F manufactured by JEOL Ltd.). The circle equivalent diameters of 500 nanoparticles were measured using image analysis software, and the average particle diameter (D50), average major axis (A50), and average aspect ratio (AR) were calculated.
[0098] Composition analysis of metal magnetic powder Samples for composition analysis were collected in a glove box, and the content of Co and other trace elements contained in the samples were measured by ICP-AES (Shimadzu Corporation: ICPS-8100CL). Based on the measurement results, the main components (elements that account for 80 wt% or more) of the metal magnetic powders were identified, and it was confirmed that all of the metal magnetic powders of Samples 1 to 24 contained 80 wt% or more of Co as the main component. In addition, it was confirmed that the metal magnetic powders of Samples 16 to 20, Sample 23, and Sample 24 contained 0.5 wt% Ru in terms of the ratio of the total content of the additive elements to the total content of Co and the additive elements, and it was confirmed that the metal powders of Samples 1 to 15, Sample 21, and Sample 22 did not contain Ru.
[0099] Crystal structure analysis by XRD An X-ray diffraction chart of the metal magnetic powder was obtained by 2θ / θ measurement using an XRD device (Rigaku Corporation: Smart Lab). The obtained X-ray diffraction chart was then analyzed using integrated X-ray analysis software (SmartLab Studio II) to determine the ratios of hcp-Co, fcc-Co, and ε-Co (W hcp , W fcc , and Wε As a result, it was confirmed that the metal magnetic powder of each of Samples 1 to 24 contained hcp-Co.
[0100] FFT image analysis For each sample, 10 nanoparticles were randomly selected from the nanoparticles contained in the metal magnetic powder, and each nanoparticle was photographed using HRTEM at an accelerating voltage of 200 kV and a magnification of 500,000 times. The lattice image of each nanoparticle was then Fourier transformed to obtain an FFT image of each nanoparticle, and it was confirmed whether the FFT image had "streak-like diffuse scattering." In the "streak-like diffuse scattering" column in Table 1 and subsequent tables, "Y" and "N" are written, and "Y" means that one or more nanoparticles having streak-like diffuse scattering were confirmed in the FFT image. On the other hand, "N" means that streak-like diffuse scattering was not observed, and other FFT patterns such as diffraction spots were observed.
[0101] Domain Size Analysis In the above-mentioned analysis of the FFT image, in the sample in which streaky diffuse scattering was observed, the average size d Ave Specifically, 10 nanoparticles were randomly selected from the nanoparticles for which streak-like diffuse scattering was confirmed, and the lattice image of each selected nanoparticle was photographed under conditions of an acceleration voltage of 200 kV and a magnification of 500,000 times. Then, in each lattice image, the position of stacking faults was identified, and the size (length) of the domain in the c-axis direction was measured. Then, from the average size of the domains in the 10 nanoparticles, d Ave , and d Ave / A50 was calculated.
[0102] Manufacturing of composite magnetic bodies For each sample in Experiment 1, a composite magnetic body was manufactured using a metal magnetic powder by the method described below. First, the metal magnetic powder and polystyrene resin were weighed out so that the content of nanoparticles in the composite magnetic body was 40 vol%. Then, the weighed metal magnetic powder, polystyrene resin, and acetone as a solvent were mixed together, and the mixture was subjected to ultrasonic dispersion treatment. The ultrasonic dispersion treatment time was 10 min, and the dispersion obtained by the ultrasonic dispersion treatment was dried in an Ar atmosphere at 50°C to obtain a dried body.
[0103] The dried body was crushed in a mortar, and the resulting granules were filled in a metal mold and pressed to obtain a composite magnetic body. In each sample of Experiment 1, the composite magnetic body had a toroidal shape with an outer diameter of 7 mm, an inner diameter of 3 mm, and a thickness of 1 mm. Each process for producing the composite magnetic body was carried out under an Ar atmosphere, except for the molding process.
[0104] The cross-sections of the composite magnetic bodies produced by the above method were analyzed, and the filling rate of the metal magnetic powder was calculated based on the area ratio of the nanoparticles. It was confirmed that the filling rate of all of samples 1 to 24 in Experiment 1 was approximately 40 vol.%, as targeted.
[0105] Analysis of composite magnetic materials A thin slice sample for TEM observation was taken from the cross section of the composite magnetic body. The thin slice sample was observed with HRTEM, and 10 nanoparticles were randomly selected from within the observation field. HRTEM and FFT images of each selected nanoparticle were then obtained under the same conditions as for the analysis of the metal magnetic powder described above. For each sample in Experiment 1, it was confirmed that the nanoparticles in the composite magnetic body had FFT images similar to the analysis results in the powder state.
[0106] Magnetic property evaluation The real part of the complex permeability (i.e., permeability μ′ (unitless)) at 1 GHz and 5 GHz was measured by the coaxial S-parameter method using a network analyzer (Agilent Technologies: HP8753D). Then, the μ′ change rate was calculated as [1-(μ′ at 1 GHz)÷(μ′ at 5 GHz)]×100. Samples with a permeability μ′ of 1.60 or more at 5 GHz and a permeability change rate of 10% or less were judged to be “good”. The evaluation results of Samples 1 to 24 in Experiment 1 are shown in Tables 1 and 2.
[0107] [Table 1]
[0108] [Table 2]
[0109] As shown in Table 1, nanoparticles having streak-like diffuse scattering were not obtained, and FFT patterns other than streak-like diffuse scattering were observed in Samples 1 to 10. In Samples 1 to 10, the permeability at 5 GHz was less than 1.60 or the μ′ change rate was greater than 10, and sufficient performance was not obtained.
[0110] In Samples 11 to 24, streak-like diffuse scattering was confirmed in the (0001) direction at [2,-1,-1,0] incidence. In other words, it was found that the FFT images of the nanoparticles in these samples had streak-like diffuse scattering. However, in Samples 11 to 15, Sample 21, and Sample 22, which did not contain the additive element M2, the permeability at 5 GHz was still less than 1.60 or the rate of change of the permeability was greater than 10, and sufficient performance was not obtained.
[0111] Among Samples 16 to 24 containing the additive element M2, Samples 16 to 19, 23, and 24, in which the nanoparticles had a D50 in the range of 1 nm to 100 nm, exhibited good performance, with a magnetic permeability of 1.60 or more and a rate of change in magnetic permeability of 10 or less at 5 GHz. In addition, in Sample 20, in which the nanoparticles had a D50 of 130 nm, the FFT image of the nanoparticles had streaky diffuse scattering, but the magnetic permeability at 5 GHz was less than 1.60 and the rate of change in magnetic permeability was greater than 10, and sufficient performance was not obtained.
[0112] The results of Experiment 1 showed that nanoparticles satisfying 1 nm≦D50≦100 nm and 1.4≦AR≦3.0 have streak-like diffuse scattering, and that containing the additive element M2 within a specified range gives them excellent magnetic properties in the high frequency band.
[0113] (Experiment 2) Samples 25-44 Metal magnetic powder and composite magnetic samples were prepared and similar measurements were carried out under the same conditions as Samples 16 to 20 in Experiment 1, except that the stirring speed during nanoparticle synthesis was adjusted within the range of 50 to 500 rpm to vary the average aspect ratio AR of the nanoparticles. The results are shown in Tables 3 and 4. It has been confirmed that the lower the stirring speed, the larger the average aspect ratio AR.
[0114] [Table 3]
[0115] [Table 4]
[0116] As shown in Tables 3 and 4, it was found that each Example in which the average aspect ratio of the nanoparticles satisfies a predetermined range tends to have a higher magnetic permeability in the high frequency band compared to each Comparative Example in which the average aspect ratio AR is large. Furthermore, from the viewpoint of magnetic permeability in the high frequency band, it was found that the average aspect ratio AR tends to be more preferable in the order of 1.4 to 2.7, 1.4 to 2.0, and 1.4 to 1.8. Furthermore, from the viewpoint of the rate of change of magnetic permeability in the high frequency band, it was found that the average aspect ratio AR tends to be more preferable in the order of 1.8 to 3.0, 2.0 to 3.0, and 2.1 to 3.0.
[0117] (Experiment 3, Experiment 4) Sample 45 to Sample 84 Nanoparticle d Ave In order to vary the / A50, metal magnetic powder and composite magnetic body samples were prepared under the same conditions as samples 16 to 39 in Experiment 2, except that the heating rate was changed, and similar measurements were performed. The results are shown in Tables 5 and 6. Note that the faster the heating rate, the greater the d Ave It was found that / A50 tends to become smaller.
[0118] [Table 5]
[0119] [Table 6]
[0120] From Tables 5 and 6, d Ave As in Experiment 2, it was found that when / A50 is within a predetermined range, excellent magnetic properties are obtained in the high frequency band.
[0121] (Experiment 5) Samples 85 to 88 Nanoparticle d Ave In order to vary the / A50, except for changing the heating rate, metal magnetic powder and composite magnetic body samples were prepared under the same conditions as sample 17 in experiment 1, and similar measurements were performed. The results are shown in Table 7.
[0122] [Table 7]
[0123] From Table 7, as in Experiments 3 and 4, d Ave When / A50 is within a predetermined range, it was found that excellent magnetic properties are obtained in the high frequency band, as in Experiment 2. Furthermore, from the viewpoint of increasing the magnetic permeability in the high frequency band, Ave It was found that the ratio d / A50 is preferably 0.006 or more and 0.1 or less. In addition, from the viewpoint of reducing the rate of change in magnetic permeability in the high frequency band, Ave It has been found that there is a favorable trend for / A50 to be 0.1 or more and 0.5 or less.
[0124] (Experiment 6) Sample 89 to Sample 112 In order to change the amount of the additive element M2 in the nanoparticles, the additive ratio of RuCl3 (additive element raw material) was changed, but other than that, metal magnetic powders and composite magnetic samples were prepared in the same manner as Samples 17, 69, 29 and 71, and similar measurements were performed. The results are shown in Table 8.
[0125] [Table 8]
[0126] From the results in Table 8, it was found that the examples in which the amount of the additive element M2 was within a predetermined range tended to have higher magnetic permeability in the high frequency band than the comparative examples. It was also found that when the ratio of the total content of the additive elements to the total content of Co and the additive elements was 0.5wt% or more and 5.0wt% or less, or 0.5wt% or more and 2.0wt% or less, it was possible to achieve both excellent levels of magnetic permeability and rate of change of magnetic permeability in the high frequency band.
[0127] (Experiment 7) Sample 113 to Sample 154 In order to change the type of additive element M2 in the nanoparticles, metal magnetic powders and composite magnetic samples were prepared in the same manner as Sample 17 and Samples 89 to 94, except that IrCl3, ReCl3, RhCl3, CrCl3, WCl4, and MoCl5 were used instead of RuCl3 (additive element raw material), and similar measurements were performed. The results are shown in Tables 9 and 10.
[0128] [Table 9]
[0129] [Table 10]
[0130] As shown in Tables 9 and 10, it was found that, as in Experiment 6, excellent magnetic properties were exhibited in the high frequency band even when the type of additive element M2 was different.
[0131] (Experiment 8) Sample 155 to Sample 394 Metal magnetic powder and composite magnetic body samples were prepared in the same manner as sample 17 in experiment 1 and sample 93 in experiment 6, except that the type and amount of additives were changed so that the nanoparticles contained multiple types of additive element M2, and similar measurements were performed. The results are shown in Tables 11 to 18. The amount of additive was such that the weight of the additive element was equal. In Tables 11 and 12, two types were included, in Tables 13 and 14, three types, in Tables 15 and 16, four types, and in Tables 17 and 18, five to seven types of additive element M2 were included.
[0132] [Table 11]
[0133] [Table 12]
[0134] [Table 13]
[0135] [Table 14]
[0136] [Table 15]
[0137] [Table 16]
[0138] [Table 17]
[0139] [Table 18]
[0140] As shown in Tables 11 to 18, even when the added element M2 contains multiple types of elements among Ru, Ir, Re, Rh, Cr, W, and Mo, it was found to provide excellent magnetic properties in the high frequency band, similar to sample 17 in experiment 1 and sample 93 in experiment 6.
[0141] (Experiment 9) Sample 395 to Sample 414 Using the metal magnetic powder made of nanoparticles of sample 89, the metal magnetic powder made of nanoparticles of sample 17, the metal magnetic powder made of nanoparticles of sample 93, and the metal magnetic powder made of nanoparticles of sample 94, the resin content ratio and molding pressure were changed to produce composite magnetic bodies with different filling rates, and similar measurements were performed in the same manner as sample 89 or sample 17, sample 93, and sample 94. The results are shown in Table 19. The cross section of the produced composite magnetic body was observed with a TEM to measure the area ratio (filling rate) of the metal magnetic powder (nanoparticles) contained in the composite magnetic body, and it was confirmed that the area ratio of the nanoparticles in each sample was approximately consistent with the value (vol%) shown in Table 19.
[0142] [Table 19]
[0143] As shown in Table 19, even when the filling rate is 10 to 60 vol%, it was found that by including the additive element M2 in a predetermined range in each example, the magnetic permeability in the high frequency band can be increased while the change in magnetic permeability can be reduced. It was confirmed that, depending on the difference in each filling rate, by including the additive element M2 in a predetermined range in this embodiment, the magnetic permeability μ′ at 5 GHz can be improved to a predetermined value or more while suppressing the rate of change in magnetic permeability to 10% or less.
[0144] For example, when the filling rate is 10 vol%, the rate of change in magnetic permeability is 10% or less and the magnetic permeability μ′ at 5 GHz can be made 1.15 or more, and when the filling rate is 20 vol%, the rate of change in magnetic permeability is 10% or less and the magnetic permeability μ′ at 5 GHz can be made 1.30 or more.
[0145] Furthermore, when the filling rate is 30 vol%, the rate of change in magnetic permeability is 10% or less and the magnetic permeability μ′ at 5 GHz can be made 1.45 or more, and when the filling rate is 40 vol%, the rate of change in magnetic permeability is 10% or less and the magnetic permeability μ′ at 5 GHz can be made 1.60 or more.
[0146] Furthermore, when the filling rate is 50 vol%, the rate of change in magnetic permeability is 10% or less and the magnetic permeability μ′ at 5 GHz can be made 1.75 or more, and when the filling rate is 60 vol%, the rate of change in magnetic permeability is 10% or less and the magnetic permeability μ′ at 5 GHz can be made 1.90 or more.
[0147] Furthermore, from the results shown in Table 19, it was confirmed that when the filling rate is 10 to 30 vol%, the rate of change in magnetic permeability can be made smaller by increasing the amount of additive element M2 to a predetermined value or more, and when the filling rate is greater than 30 vol% and less than 60 vol%, the magnetic permeability μ' at 5 GHz can be made larger by increasing the amount of additive element M2 to a predetermined value or more.
[0148] (Experiment 10) Sample 415 to Sample 426 In order to change the type of additive element M2 in the nanoparticles, IrCl3, ReCl3, RhCl3, CrCl3, WCl4, and MoCl5 were used instead of RuCl3 (additive element raw material), but metal magnetic powder and composite magnetic samples were prepared in the same manner as samples 69 and 88, and similar measurements were performed. The results are shown in Table 20.
[0149] [Table 20]
[0150] From Table 20, as in Experiment 5, d Ave When / A50 is within a predetermined range, it was found that excellent magnetic properties are obtained in the high frequency band, as in Experiment 2. Furthermore, from the viewpoint of increasing the magnetic permeability in the high frequency band, Ave It was found that the ratio d / A50 is preferably 0.006 or more and 0.1 or less. In addition, from the viewpoint of reducing the rate of change in magnetic permeability in the high frequency band, Ave It has been found that there is a favorable trend for / A50 to be 0.1 or more and 0.5 or less. [Explanation of symbols]
[0151] 2. Nanoparticles 10 … Composite magnetic material 6 ... Resin 100 … Inductor 50 ... Coil section 60,80 … external electrode
Claims
1. The nanoparticles contain Co as a main component and have an average particle size (D50) of 1 nm or more and 100 nm or less, a Fourier transform image using a lattice image of the nanoparticles has streak-like diffuse scattering, Contains at least one additive element selected from the group consisting of Ru, Ir, Re, Rh, Cr, W, and Mo; The ratio of the total content of the additional elements to the total content of Co and the additional elements is 0.5 wt % or more and 10 wt % or less, The metal magnetic powder has an average aspect ratio (AR) of the nanoparticles in a TEM image of 1.4 or more and 3.0 or less.
2. The average size of the domains present inside the nanoparticles is defined as dAve, The average major axis of the nanoparticles is A50, 2. The metal magnetic powder according to claim 1, wherein the ratio of dAve to the average major axis of the nanoparticles (dAve / A50) is 0.006 or more and 0.5 or less.
3. A composite magnetic body comprising the metal magnetic powder according to claim 1 or 2.
4. An electronic component comprising the metal magnetic powder according to claim 1 or 2.
Citation Information
Patent Citations
Magnetic material and magnetic device
JP2006303298A